Fabrication of 3D GelMA Scaffolds Using Agarose Microgel Embedded Printing - Bo Yang; Tianqi Liu; Ge Gao; Xianglin Zhang; Bin Wu (Micromachines, 2022)
Photocrosslinked Gelatin–Methacryloyl (GelMA) has been widely used in the field of 3D bioprinting due to its excellent biological properties, but its properties are not yet optimized. With the advent of embedded printing, the balance between hydrogel printability and cell viability is expected to be achieved. Agarose microgel is a good support material because of its simple preparation, good biocompatibility, high melting point, and good rheology. In this study, aiming at realizing a GelMA/Agarose suspension printing system, the printing effect of the suspension process was explored, and a suitable process printing window was defined. The resulting scaffolds showed better water absorption and elasticity, but larger deformation during printing. This study explored some potential roles of suspension baths in embedded printing, paving the way for the preparation of good suspension structures that can be convenient for customized tissue engineering applications.